العلاقـة بيـن نظافـة العامليـن وتلـوث منتجـات الالبـان - اسماعيل, صفوت جميل; الياس, حنان متي; الوندي, صلاح الدين برهان (Al-Nahrain Journal of Science, 2018)
The milk and dairy food a basic human, and the need to provide this food clean and free from contamination of food within the principle of food safety risks and for the purpose of the causes and sources of contamination and how we address this epidemiological study sites in the productivity of workers on production and the immediate withdrawal of bacteriological swabs of the hands and throat of workers and examine the product on the production lines of the workers themselves and testing for skin cluster (Staphylococcus) and examination of the colon bacteria (Coliform) of swabs and samples of production workers. The results of the study showed that the liquid milk product in sterile glass bottles, and cheese free of bacterial contamination have nothing to do with these workers two productes contamination.The results showed the presence of contamination in the yogurt and cream. The relationship between the contamination and working with the contamination of varying degrees while the results showed a direct relationship between employees and soft cheese and butter. Deduce the need for careful attention to hygiene workers to direct the production lines and bringing them medical laboratory tests with the radical paws focus on the use of protective masks and sterile materials and attention to hygiene and reliance on automation at all stages of production process help reduce contamination in the final product.